Knowledge and attitude factors as determinants of pregnant women’s participation in triple elimination program in North Bali - Sekarini Ni Nyoman Ayu Desy; Yanti Linda; Pratiwi Putu Irma (BIO Web of Conferences)
In 2022, Bangkalan District had the lowest basic immunization coverage in East Java, with 64.7%, compared to the statewide average of 91.7%. This low coverage, which increases the risk of morbidity and mortality, is the result of misconceptions about immunizations. The WHO reports that 1.5 million children die annually from diseases that may have been avoided if they had received the vaccination, highlighting the broader public health implications. This study looked at the socioeconomic and cultural factors influencing parents’ decisions to vaccinate their children in Bangkalan. As part of a cross-sectional study, 87 mothers of toddlers older than two years from the Blega Health Center were selected using simple random selection. Results indicated that knowledge and attitudes significantly influence participation (P-value < 0.05). Higher knowledge levels and positive attitudes toward prevention correlate with increased participation in the program. These findings highlight the need for education-based interventions to improve knowledge and address negative attitudes. Enhancing awareness is crucial to promote active participation and achieve the program’s goals in North Bali.